2007
DOI: 10.2151/jmsj.85.101
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Tropospheric Circulation over the Western North Pacific and Tropical Cyclone Approach/Landfall on Japan

Abstract: The relationship between large-scale seasonal (June-October) circulation over the western North Pacific, and the frequency of tropical cyclone (TC) approach or landfall on Japan, is examined using the reanalysis datasets (ERA-40(1958(ERA-40( -2001 and JRA-25(1979JRA-25( -2004). The result shows that there are two dominant modes over the western North Pacific; the El Niñ o Southern Oscillation (ENSO) mode, and a mode that is correlated with the variation of the subtropical high. In years when the subtropical hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 10 publications
1
22
0
Order By: Relevance
“…As an example, Fig. 3 exhibits the tracks of 26 TCs in 2001 when indicative of El Ni˜na, frequency no/La Niõ f landfalling TCs in the main islands of Japan and frequency of TC genesis in the western North Pacific were neutral (Nakazawa and Rajendran 2007). The best track data reported that 13 (50%, dots in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…As an example, Fig. 3 exhibits the tracks of 26 TCs in 2001 when indicative of El Ni˜na, frequency no/La Niõ f landfalling TCs in the main islands of Japan and frequency of TC genesis in the western North Pacific were neutral (Nakazawa and Rajendran 2007). The best track data reported that 13 (50%, dots in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have investigated the relationship between the extent of the Pacific high and TC tracks (e.g., Harr and Elsberry 1995;Nakazawa and Rajendran 2007). In particular, Kawatani et al (2008) used monthly means to show that more TCs occur near Taiwan, Okinawa (southwest of Kyushu), and the Philippines when the Pacific high extends further westward; conversely, more TCs occur to the east of these areas when the Pacific high retreats further eastward.…”
Section: Tropical Cyclones and The Extension Of The Pacific Highmentioning
confidence: 99%
“…Typhoon Songda (2004) was 1 of the 10 named typhoons that made landfall on the main islands of Japan in 2004 and brought extensive damage to Japan due to both strong winds and heavy rainfall (Nakazawa and Rajendran 2007). Te storm formed near the Marshall Islands on 27 August 2004 and moved northwestward over the western North Pacific.…”
Section: An Overview Of Typhoon Songdamentioning
confidence: 99%